Reflexive learning and performative failure. Issue 3 (July 2020) - Parker, Simon; Racz, Marton; Palmer, Paul
In this article, we emphasize the importance of context for student learning. Based on reflective logs and interview data, we explore how students learn outside of the classroom as they undertake an experiential dissertation project. We identify three different forms of reflexive learning and critique, all triggered by some form of performative failure; scholarly critique, engaged critique and engaged action . Drawing on Butler's theory of performativity, we illustrate how reflexivity is not purely the action of any individual student, rather it is a practice that is co-created within a certain context. As such, we contest individualistic understandings of reflexivity and encourage a careful consideration of the places students and managers are encouraged to be reflexive.